Soil-transmitted helminth infections, anemia and undernutrition among schoolchildren in Yirgacheffee, South Ethiopia - Molla, Eshetu (BMC Res Notes, 2018)
OBJECTIVE: Current data on soil-transmitted helminth infections, anemia and malnutrition that are largely neglected is vital to the control and management of them in a specific setting. This study was, therefore, aimed at determining the status of the three health concerns in one of the high-risk groups, schoolchildren, in South Ethiopia. RESULTS: Among the 443 sampled schoolchildren, 54% were infected with soil-transmitted helminths (STHs) and 15.4% of them had anaemia, while the prevalence rate of undernutrition was 28.9%. Species-wise, prevalence of STH infections was 21.7, 16.7, 7.2 and 8.4% for Ascaris lumbricoides, the hookworms, Trichuris trichiura and mixed infections, respectively. Untreated drinking water, high frequency of sucking fingernails and open defecation were significantly associated with risk of getting STH infections. Child positivity for STH infection didn’t show any significant association with undernutrition of the children. Anaemia was significantly correlated with hookworm (adjusted odds ratio (AOR) = 2.96, 95% confidence interval (CI) = 2.15, 4.86), A. lumbricoides (AOR = 1.93, 95% CI = 1.13, 3.01) and polyparasitism (AOR = 1.54, 95% CI = 1.04, 2.64). In addition, children with heavy intensities of hookworm infections and those undernourished were more likely to suffer from anaemia with P = 0.001 and P = 0.007, respectively.